2014
DOI: 10.1038/srep04765
|View full text |Cite
|
Sign up to set email alerts
|

Potent hepatitis C inhibitors bind directly to NS5A and reduce its affinity for RNA

Abstract: Hepatitis C virus (HCV) infection affects more than 170 million people. The high genetic variability of HCV and the rapid development of drug-resistant strains are driving the urgent search for new direct-acting antiviral agents. A new class of agents has recently been developed that are believed to target the HCV protein NS5A although precisely where they interact and how they affect function is unknown. Here we describe an in vitro assay based on microscale thermophoresis and demonstrate that two clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 36 publications
3
99
0
1
Order By: Relevance
“…An additional report of direct binding to NS5A protein of DCV and the related compound ledipasvir also supports the direct association of NS5A RCIs with the NS5A protein (8). Immunomicroscopy analysis indicates that DCV binding results in the apparent disassociation of NS5A from the replication complex, consistent with other evidence that NS5A RCI binding has multiple effects (9-13).The use of functional NS5A affinity reagents (inhibitory crosslinkers, labeled NS5A proteins) and genetic variants has provided evidence for the presence of NS5A dimers and oligomers in cells, suggesting that NS5A-NS5A dimers may be necessary for HCV replication and NS5A function (7,14,15). Experiments using NS5A constructs tagged near domain 1 for binding of fluorescent labels detected a correlation between inhibitor activity and changes in fluorescent signal that is consistent with conformational changes in NS5A upon compound binding (14).…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…An additional report of direct binding to NS5A protein of DCV and the related compound ledipasvir also supports the direct association of NS5A RCIs with the NS5A protein (8). Immunomicroscopy analysis indicates that DCV binding results in the apparent disassociation of NS5A from the replication complex, consistent with other evidence that NS5A RCI binding has multiple effects (9-13).The use of functional NS5A affinity reagents (inhibitory crosslinkers, labeled NS5A proteins) and genetic variants has provided evidence for the presence of NS5A dimers and oligomers in cells, suggesting that NS5A-NS5A dimers may be necessary for HCV replication and NS5A function (7,14,15). Experiments using NS5A constructs tagged near domain 1 for binding of fluorescent labels detected a correlation between inhibitor activity and changes in fluorescent signal that is consistent with conformational changes in NS5A upon compound binding (14).…”
mentioning
confidence: 49%
“…A recent report (7) of DCV binding to Escherichia coli-expressed NS5A protein provided the first direct evidence that DCV binds to NS5A. The authors demonstrated that DCV binding can reduce the affinity of NS5A protein for viral RNA, supporting one potential mechanism of inhibition.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The cytoplasmic part of NS5A is composed of a well structured domain 1 (D1) and two intrinsically disordered domains (D2 and D3) that exist as highly dynamic interconverting conformers. NS5A-D1, which is the target of daclatasvir (7,17), contains a zinc finger motif and possesses RNA binding properties (18). Crystallographic studies revealed that this domain could adopt at least three different homodimeric conformations (19 -21), underscoring the multifunctionality of the protein.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%